Telehealth Practice Policies need to be Strengthened to Achieve Better Quality and Accessibility of Care in the Post COVID-19 Pandemic: A Rapid Review - Dwi Raharjo, Untoro; Ariningtyas , Ristiana Eka; Rosyad, Yafi Sabila (Journal of health research and technology, 2023)
Digital health services in healthcare facilities have been escalated during the COVID-19 pandemic. Telehealth has become one of the fastest adopted information and communication technologies (ICT) and is projected as a future solution to provide better healthcare services. In Indonesia, the implementation of telehealth had been initiated before the COVID-19 pandemic but did not explicitly mention specific healthcare professionals. This situation has led to unclear boundaries for telehealth practice among healthcare professionals while the implementation of telehealth is still encouraged. Therefore, our aim was to identify alternatives to strengthen the policies that support the implementation, quality, and accessibility of telehealth in Indonesia. We conducted a rapid review of articles related to telehealth implementation and policies that had been published on Portal Garuda, EBSCOHost, Pubmed, and Google Scholar. We also considered articles with an MMAT score >80 as eligible articles that could be included in the synthesis. Our findings have been crystallized into several ideas, one of which is that the implementation of telehealth must be supported by three aspects: organizational support, equity, and legal support. We recommend some alternatives such as training, policy and guideline strengthening, data security improvement, and funding to accelerate telehealth implementation in Indonesia. In conclusion, although some policies have been implemented to support telehealth in Indonesia after the COVID-19 pandemic, these policies are still weak in protecting other healthcare professionals' practice through telehealth, except for doctors. Specific guidelines and stronger policies are needed.